Sit-To-Stand (STS) timing among older adults in their homes: Two measurement approaches - Grant, Theresa L; Bryanton, Megan; Taylor, Matthew; Sveistrup, Heidi; Bilodeau, Martin; Knoefel, Frank; Goubran, Rafik; Jutai, Jeffrey (Université d'Ottawa | University of Ottawa, 2014)
Sit-to-stand (STS) times required by older adults exiting from their beds at home were compared simultaneously using under mattress pressure sensor technology and video analysis. Six older adults consented to participate in the study and had under mattress pressure technology installed in their homes. Participants were visited monthly over a period of 2-10 months by a researcher who asked them to perform three bed exits which were videotaped. The pressure sensor technology calculated a portion of STS time based on changes in pressure between the end of stable sitting on the edge of the bed and pressure leaving the bed. The video analysis approach calculated this corresponding initial phase of the same STS transfer by determining the difference between the first forward movement from the quiet sitting position and the initiation of vertical rise. The remaining period of vertical rise into a complete standing position was calculated using video analysis but not pressure sensor technology. A Spearman’s rank order correlation analysis revealed that there was a moderate, positive correlation between the video and pressure-sensor measures of the initial phase of STS which was statistically significant (rs=0.50, n=97, p<0.001). Wilcoxon signed-rank tests indicated that pressure sensor times were longer (Z=-7.91, p<0.000) and more variable than video times (Z=-3.14, p=0.002). Analysis of video data revealed that this initial phase of STS represented between 15 to 81% of the total STS time among the 97 sampled STS in this study. Results highlight how the home environment presents a number of conditions affecting differences in STS values obtained by each of these measurement approaches.
Keywords: home monitoring; under mattress pressure sensors; sit-to-stand; aging